2018
DOI: 10.1038/s41598-018-21836-6
|View full text |Cite
|
Sign up to set email alerts
|

Onset and Evolution of Southern Annular Mode-Like Changes at Centennial Timescale

Abstract: The Southern Westerly Winds (SWW) are the surface expression of geostrophic winds that encircle the southern mid-latitudes. In conjunction with the Southern Ocean, they establish a coupled system that not only controls climate in the southern third of the world, but is also closely connected to the position of the Intertropical Convergence Zone and CO2 degassing from the deep ocean. Paradoxically, little is known about their behavior since the last ice age and relationships with mid-latitude glacier history an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
149
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(168 citation statements)
references
References 50 publications
18
149
1
Order By: Relevance
“…This study is based on sediment cores from Lago Cipreses (cores PS0710SC1 + PS0710AT1-3, 365 cm depth) reported in Moreno et al (2018), Lago Guanaco (cores PS0404SC + PS0711GT1-7, 519 cm depth) reported in Moreno et al (2010), and Vega Ñandú (cores PS0405RC1A + PS0303AT1-4, 400 cm depth) reported in Villa-Martínez and . These consist of organic silts in the case of Lago Cipreses and Lago Guanaco, and various transitions from organic mud and peat in the case of Vega Ñandú.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is based on sediment cores from Lago Cipreses (cores PS0710SC1 + PS0710AT1-3, 365 cm depth) reported in Moreno et al (2018), Lago Guanaco (cores PS0404SC + PS0711GT1-7, 519 cm depth) reported in Moreno et al (2010), and Vega Ñandú (cores PS0405RC1A + PS0303AT1-4, 400 cm depth) reported in Villa-Martínez and . These consist of organic silts in the case of Lago Cipreses and Lago Guanaco, and various transitions from organic mud and peat in the case of Vega Ñandú.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of Vega Ñandú we obtained the upper meter with a D-section Russian corer and the remaining section with a Wright square-rod piston corer. All sedimentary material was sent to the Quaternary paleoecology laboratory at Universidad de Chile and stored in a cold room at 4 • C. We documented the core stratigraphies with the aid of X-radiographs and textural descriptions of the sediments (Villa-Martínez and Moreno et al, 2010Moreno et al, , 2018.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other SAM indices (or SH pressure / wind estimates) have been reconstructed over much longer time periods, many spanning back to AD 1000, using midlatitude proxy data such as tree rings and lake sediments (J. M. Jones & Widmann, 2003; Moreno et al, 2018; Villalba et al, 2012), ice core proxy data from Antarctica (I. D. Goodwin et al, 2014; I. D. Goodwin et al, 2004; Yang & Xiao, 2018), or multiproxy reconstructions based on a combination of midlatitude and Antarctic data (Abram et al, 2014; Zhang et al, 2010). Notably, as seen in South American (G. Silvestri & Vera, 2009) and Antarctic (G. J. Marshall et al, 2011, 2013) temperatures, recent work also suggests that many paleo–proxy relationships with the SAM are likely to be nonstationary, although this relationship varies regionally (Dätwyler et al, 2018).…”
Section: Past Characteristics Of the Sammentioning
confidence: 99%
“…During this phase of moderate/higher temperatures, the reconstructed Southern Annular Mode (SAM) [119] has also exhibited less negative values. The core zone of the Southern Hemispheric Westerlies is located between 50 and 55 • S. In a positive phase of the SAM, this windbelt contracts towards the pole and weakens the winds between 40 and 50 • S, and vice versa [1,123]. After 1350 A.D., a significant decrease in the reconstructed temperature and also a prolonged period of exceptionally negative SAM indices can be considered to mark the (climatological) onset of the LIA.…”
Section: Late Holocene Glacial Oscillations In Southernmost Americamentioning
confidence: 99%